2014
DOI: 10.1016/j.eplepsyres.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Tumor associated seizures in glioblastomas are influenced by survival gene expression in a region-specific manner: A gene expression imaging study

Abstract: Tumor associated seizures (TAS) are common and cause significant morbidity. Both imaging and gene expression features play significant roles in determining TAS, with strong interactions between them. We describe gene expression imaging tools which allow mapping of brain regions where gene expression has significant influence on TAS, and apply these methods to study 77 patients who underwent surgical evaluation for supratentorial glioblastomas. Tumor size and location were measured from MRI scans. A 9-set gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In our cohort, there were no significant differences regarding tumoral GM or WM involvement between the groups. In brief, all of these findings support the fact that tumor location plays an important role in developing seizures in GBM .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In our cohort, there were no significant differences regarding tumoral GM or WM involvement between the groups. In brief, all of these findings support the fact that tumor location plays an important role in developing seizures in GBM .…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies proposed that glial tumors located in frontal, parietal, insular and temporal lobes were more epileptogenic . However, most of these studies did not use a volumetric imaging analysis for precise localization of seizure‐related regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to an epileptic susceptibility or gene that may have played a role in epileptogenesis, as has been previously suggested. [ 1 , 6 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that such mutations cannot solely explain the favorable prognosis of epileptogenic glioblastomas [7]. A lower expression of OLIG2 , linked to the proneural GBM subtype [3], was also related to an increased risk of tumor-associated seizures [19]. How this could relate to the prognosis is however unknown.…”
Section: Introductionmentioning
confidence: 99%